The Apparent Asymmetrical Relationship Between Small Bowel Bacterial Overgrowth, Endotoxemia, and Liver Steatosis and Fibrosis in Cirrhotic and Non-Cirrhotic Patients: A Single-Center Pilot Study - Scarpellini, E.; Abenavoli, L.; Cassano, V.; Rinninella, E.; Sorge, M.; Capretti, F.; Rasetti, C.; Svegliati Baroni, G.; Luzza, F.; Santori, P.; Sciacqua, A. (Frontiers in Medicine, 2022)
Gut microbiota is a complex ecosystem harboring our intestine. It maintains human body equilibrium while its derangement, namely “ dysbiosis “, has been associated with several gastrointestinal diseases such as liver steatosis (NAFLD) until liver cirrhosis. Small intestinal bacterial overgrowth (SIBO) is an example of dysbiosis of the upper gastrointestinal (GI) tract. To evaluate the relationship between SIBO and levels of endotoxemia and grade of liver steatosis (LS) and fibrosis (LF) in hepatologic patients. Consecutive outpatients referred to our Hepatology clinic have been tested for SIBO by lactulose breath test and peripheral blood levels of endotoxemia; LS grading and LF were assessed by abdominal ultrasound and transient elastography, respectively. Fifty-two consecutive patients (15 with alcoholic abuse, 4 with HCV- and 2 with HBV-infection, 22 of metabolic origin, 4 of autoimmune origin, and 5 with cholangiopathies; mean age 54.7±8.3 years, 31 F, BMI 24.1±1.1 Kg/m2) and 14 healthy volunteers (HV) (mean age 50.1±4.3 years, 9 F, BMI 23.3±1.1 Kg/m2) were enrolled. SIBO prevalence was significantly higher in cirrhotic (LC) vs. non-cirrhotic (LNC) patients and vs. HV (all, p<0.05), with a significant positive trend according to Child-Pugh status (all, p<0.05). SIBO prevalence was not correlated with LS stages (all, p=NS). Consensually, endotoxin levels were significantly higher in LC vs. LNC and vs. HV (all, p<0.05) and significantly correlated with LF in LC patients, according to Child-Pugh status (all, p<0.05). The present study shows SIBO prevalence and relative endotoxin blood levels are significantly associated with the grade of LF vs. LS in LC. SIBO is present also in pre-cirrhotic conditions but its prevalence seems to correlate with liver disease irreversible derangement.